Imprison'd wranglers the rhetorical culture of the House of Commons 1760-1800 - Reid, Christopher, 1952- (Oxford : Oxford University Press, 2013)
'Imprison'd Wranglers' is a detailed study of parliamentary speaking in its golden age at the end of the 18th century. The book looks closely at the physical and political conditions in which these men spoke, and the techniques they used to discredit the arguments of their opponents and to move and convince their audience in the House.
Description based on online resource; title from home page (viewed on Dec. 14, 2012).
Includes bibliographical references and index.
Keywords: Political oratory -- Great Britain -- History -- 18th century; Great Britain. -- Parliament. -- House of Commons -- History -- 18th century